Analisis Hukum Administrasi Terhadap Kebijakan Pemerintah Mengenai Pembebasan Biaya Sertifikasi Tanah Wakaf - Islamiyati Islamiyati (Administrative Law and Governance Journal, 2019)
Abstrack The study analyzed Article 22 of Government Regulation Number 13 of 2010 concerning government policies for the exemption of waqf land certification fees according to state administrative law. The analyze focus on the reasons for the government to issue such policies in the perspective of the state administrative law. The research type of library research requires secondary data, which consists of primary, secondary and tertiary legal materials, normative juridical approaches, and qualitative data analysis. The results of the study explained that the government issued a policy of freeing the cost of waqf land certificates aimed at empowering waqf land so that its designation could be felt by the community, accelerating the legality of waqf land, protecting and securing and optimizing the benefits of waqf assets. This policy is an effort to understand waqf deeds which means worship and legal certainty. Government policy is the implementation of the function of the  state administrative law in creating a government that is clean and in accordance with the principles of good general governance, namely; the principles of legality, equality, justice, legal protection, wisdom, implementation of public interest, and acting meticulously. Key Words: State Administrative Law, Free of Cost, Endowments Land Certification Abstrak Penelitian menganalisis Pasal 22 Peraturan Peemrintah Nomor 13 Tahun 2010 tentang kebijakan pemerintah pembebasan biaya sertifikasi tanah wakaf menurut hukum administrasi negara. Menganalisis alasan pemerintah mengeluarkan kebijakan demikian dalam perspektif HAN. Jenis penelitian library research, memerlukan data sekunder, yang terdiri dari bahan hukum primer, sekunder dan tersier, pendekatannya yuridis normatif, dan analisis datanya kualitatif. Hasil penelitian menjelaskan bahwa pemerintah mengeluarkan kebijakan  membebaskan biaya sertifikat tanah wakaf bertujuan untuk memberdayakan tanah wakaf supaya peruntukannya dapat dirasakan masyarakat, percepatan legalitas tanah wakaf, melindungi dan mengamankan serta mengoptimalkan manfaat aset wakaf. Kebijakan ini adalah salah satu upaya memahami perbuatan wakaf yang bermakna ibadah dan berkepastian hukum. Kebijakan pemerintah merupakan implementasi fungsi HAN dalam menciptakan pemerintahan yang bersih dan sesuai asas pemerintahan umum yang baik, yakni; asas legalitas, kesamaan, keadilan, perlindungan hukum, kebijaksanaan, penyelenggaraan kepentingan umum, dan bertindak cermat. Kata Kunci: Hukum Administrasi Negara, Bebas Biaya, Sertifikasi Tanah Wakaf